Pengaruh Kualitas Jasa Terhadap Kepuasan Nasabah Pada Bank Umum Syariah di Surakarta - Ulul Azmi Mustofa; Yudi Siyamto (Jurnal Ilmiah Ekonomi Islam, 2015)
The purpose of this study was to determine whether there is influence of service quality on customer satisfaction Islamic banks, so as to identify which dimension of service quality that is dominant in influencing customer satisfaction.Variables used consists of dimensional compliance, assurance, reliability, tangible, empathy and responsiveness known  CARTER name. This research was conducted in the region with a population Surakarta Islamic commercial bank customers are categorized as foreign banks with a sample of 90 respondents, as well as the sampling process is done by accidental sampling.The results showed that partially dimensional compliance, reliability, tangibility, empathy, responsiveness individual has an influence on customer satisfaction Islamic commercial bank. As for the variables assurance there are no significant effects. In this case the use CARTER dimension is good enough since it simultaneously has the effect on customer satisfaction.Keywords: Service Quality, Customer Satisfaction, CARTER